Improving Employee Performance Through Providing Additional Employee Income and Work Environment - Nailatul Ilmi Nafi’ah; Mochamad Arifianto; Nurul Qomariah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
Providing additional incentives outside of salary usually makes employees enthusiastic at work. A comfortable work environment is also the dream of every worker or employee in every organization. This study aims to determine the impact of additional employee income and a comfortable work environment on the performance of an employee at the Employment, Education and Training Agency in Banyuwangi Regency. This research is a quantitative study with all Civil Servants in the Personnel, Education and Training Agency as a sample of 36 civil servants. The analysis technique is by conducting multiple linear regression tests and hypothesis testing, using SPSS Statistic V. 29.0.0.0 Software. The results of the research based on the results of the calculations show that the provision of additional income in the form of incentives has an impact on employee performance. Meanwhile, a comfortable work environment has no effect on the performance of the Banyuwangi Regency Personnel, Education and Training Agency employees.